A CGIF negative carbon filling material and preparation method
By utilizing the porous structure of CGIF negative carbon filling materials and the bonding effect of cementitious materials during underground coal mining, the problem of difficulty in comprehensive utilization of coal-based solid waste with existing technology is solved, and efficient CO2 storage and efficient coal gangue storage are achieved. use.
Patent Information
- Application Number
- CN202311163944.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-09-11
AI Technical Summary
It is difficult for the existing technology to comprehensively utilize the space formed by underground coal mining and coal-based solid waste such as coal gangue and fly ash to synthesize negative carbon filling materials with high porosity, high strength and high CO2 storage rate.
CGIF negative carbon filling material is used, which includes bulk coal gangue and cementitious materials. Through the bonding effect of cementitious materials between coal gangue particles, the porosity is not less than 30% and the uniaxial compressive strength is not less than 0.46. MPa coal gangue-colloid composite porous material uses its porous structure to store CO2.
It has realized a negative carbon filling material with high porosity, low density and high strength, with a CO2 storage rate of not less than 25%. It also reduces the cost of coal gangue crushing and improves the overall efficiency of the mine.
Smart Images

Figure CN117229023B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of resource utilization of coal mine solid waste and negative carbon technology, and in particular to a CGIF negative carbon filling material and a preparation method thereof. Background Art
[0002] The mining process of coal resources will produce a large amount of CO2 and coal-based solid wastes such as coal gangue and fly ash. Backfill mining technology is one of the important technologies for achieving green and low-carbon mining. It has significant advantages in rock movement control, ecological environmental protection, and coal-based solid waste disposal and utilization, and has therefore achieved good development. Backfill mining technology is divided into comprehensive mechanized solid filling, comprehensive mechanized paste filling, longwall cemented filling, subsequent space gangue grouting filling, underground mining and filling + X technology, etc. Each filling method has different applicable conditions and advantages and disadvantages, and the filling system, equipment, filling process, etc. are also very different.
[0003] Underground mining, selection and filling + X technology refers to achieving the "X" goal while integrating low-gangue mining, coal gangue sorting and gangue filling. "X" can be a specific technology or process, a goal achieved based on mining, selection and filling technology, or an improvement in the intelligence level of the entire or partial mining and filling system. When "X" is negative carbon mining, underground mining, selection and filling + X technology can be expressed as coal-based solid waste filling underground carbon sequestration technology. Utilizing the space formed by underground coal mining to treat coal-based solid waste and CO2, developing new negative carbon filling materials to increase the carbon fixation rate, and turning waste into treasure are of great theoretical and practical significance for promoting the sustainable development of green and low-carbon technologies. Summary of the invention
[0004] Technical problem: Provide a negative carbon filling material and its preparation method to comprehensively utilize the space formed by underground coal mining and coal-based solid waste such as coal gangue and fly ash to synthesize a negative carbon filling material with high porosity, high strength and high CO2 storage rate.
[0005] Technical solution:
[0006] On the one hand, a CGIF (CO2 Gangue Inorganic Framework) negative carbon filling material is provided, which is a negative carbon filling body that uses the high porosity structure of gangue to seal liquid / supercritical CO2, and comprises loose coal gangue and a cementitious material, wherein the particle size of the loose coal gangue is 0 to 20 mm, the cementitious material is attached to the surface of the loose coal gangue in a flocculent state, and the key contact points between the particles of the loose coal gangue are bonded by the cementitious material, and the loose coal gangue and the The cementitious materials are connected layer by layer to form a gangue-colloid composite porous material with a porosity of not less than 30% and a uniaxial compressive strength of not less than 0.46MPa, namely, a negative carbon filling material; the porous structure in the negative carbon filling material can be used to store CO2, and the CO2 storage rate is not less than 25%; wherein: the slump of the cementitious material is between 170 and 200mm, the initial setting time is less than 15min, the final setting time is less than 3h, and it has fast and efficient bonding and is not easy to flow.
[0007] The present invention utilizes the porous space of CGIF negative carbon filling materials to achieve the structural storage of CO2, and utilizes the structural strength of 0-20 mm coarse-grained coal gangue and the bonding effect of cementitious materials to simultaneously achieve low density and high strength bearing of the negative carbon filling materials.
[0008] In some embodiments, the cementitious material includes the following components, measured by mass: 100-140 parts of fly ash, 10-15 parts of cement, 70-90 parts of quicklime, 1.5-2.5 parts of cement early strength activator, 3-5 parts of accelerator and 50-60 parts of water.
[0009] In some embodiments, the cementitious material includes the following components, measured in parts by mass: 120 parts of fly ash, 10 parts of cement, 80 parts of quicklime, 2 parts of cement early strength activator, 4 parts of accelerating agent and 54 parts of water.
[0010] In some embodiments, the loose coal gangue is obtained by sorting coal gangue with a particle size of ≤200 mm in a mining area or crushing coal gangue accumulated on the surface.
[0011] On the other hand, a method for preparing the aforementioned negative carbon filling material is provided, comprising the following steps:
[0012] (1) according to the target porosity of the negative carbon filling material, filling the negative carbon filling material mold with the loose coal gangue of a certain particle size distribution;
[0013] (2) closing the bottom grouting hole of the negative carbon filling material mold, and injecting liquid / supercritical CO2 (i.e., the physical state of CO2 is liquid or supercritical) from the top grouting hole of the negative carbon filling material mold; recording the CO2 injection volume V1, and calculating the carbon sequestration rate Φ of the negative carbon filling material;
[0014] (3) injecting the cementitious material from the top grouting hole of the negative carbon filling material mold until the cementitious material fills the negative carbon filling material mold;
[0015] (4) opening the bottom slurry discharge hole of the negative carbon filling material mold to discharge excess cementitious material to obtain the negative carbon filling material sample;
[0016] (5) After the negative carbon filling material sample is placed in a curing box and cured for 1 hour, the uniaxial compressive strength σ and porosity θ of the negative carbon filling material are tested;
[0017] (6) By changing the particle size distribution of the loose coal gangue in step (1) to change the target porosity of the negative carbon filling material, repeating steps (2) to (5), a prediction model between the porosity θ, carbon sequestration rate Φ and uniaxial compressive strength σ of the negative carbon filling material is established, as shown in the following formula:
[0018] σ=F(θ,Φ);
[0019] (7) According to step (6), the particle size distribution of the loose coal gangue corresponding to the method of selecting the negative carbon filling material having a porosity θ not less than 30%, a uniaxial compressive strength σ not less than 0.46 MPa and a CO2 storage rate Φ not less than 25% is selected.
[0020] In some embodiments, the particle size gradation of the loose coal gangue is 0 to 20 mm.
[0021] In some embodiments, the particle size gradation of the loose coal gangue is 0-10 mm; the porosity θ of the obtained negative carbon filling material is not less than 30%, the uniaxial compressive strength σ is not less than 0.6 MPa, and the CO2 storage rate Φ is not less than 25%.
[0022] In some embodiments, the particle size gradation of the loose coal gangue is 0-15 mm; the porosity θ of the obtained negative carbon filling material is not less than 49%, the uniaxial compressive strength σ is not less than 0.5 MPa, and the CO2 storage rate Φ is not less than 36%.
[0023] In some embodiments, the negative carbon filling material mold is transparent, which facilitates observation of the state of the loose coal gangue and cementitious material inside.
[0024] In some embodiments, the negative carbon filling material mold is a standard cube with a side length of 70.7 mm.
[0025] In some embodiments, the top grouting holes and the bottom grouting holes of the negative carbon filling material mold are circular holes, the number of the top grouting holes and the number of the bottom grouting holes are 5 respectively, and the top grouting holes and the bottom grouting holes can be opened and closed.
[0026] In some embodiments, the diameter of the top grouting hole and the bottom grouting hole is 6 mm.
[0027] In some embodiments, in step (2), when injecting liquid / supercritical CO2, if the local pressure is too high and the liquid / supercritical CO2 is difficult to inject, other top grouting holes are replaced to continue injecting liquid / supercritical CO2;
[0028] In some embodiments, in step (3), when injecting the cementitious material, the cementitious material is injected sequentially from top grouting holes at different positions to improve the distribution uniformity of the cementitious material in the negative carbon filling material mold.
[0029] Beneficial effects: Compared with the prior art, the negative carbon filling material of the present invention has the following advantages:
[0030] (1) The present invention provides a negative carbon filling material and a preparation method thereof, which comprehensively utilizes the space formed by underground coal mining and coal-based solid wastes such as coal gangue and fly ash, and successfully synthesizes a negative carbon filling material with high porosity (not less than 30%), high strength (uniaxial compressive strength not less than 0.46 MPa) and high CO2 storage rate (not less than 25%), which is conducive to achieving high-efficiency negative carbon filling under the conditions of safe and efficient coal mining.
[0031] (2) The present invention utilizes the high viscosity and non-flowability characteristics of cementitious materials with a slump between 170 and 200 mm, an initial setting time of less than 15 minutes, and a final setting time of less than 3 hours. The loose coal gangue interacts with the cementitious materials to form a strong bonding effect between the key contact points between the particles of the loose coal gangue, and finally forms a coal gangue-colloidal composite porous material filling body with a large number of pores and a stable overall structure as follows: the cementitious materials are attached to the surface of the loose coal gangue in the form of flocs, and are bonded by the cementitious materials at the key contact points between the particles of the loose coal gangue, and the loose coal gangue and the cementitious materials are connected layer by layer.
[0032] (3) Different from the existing cementing filling materials in which the particle size of gangue does not exceed 10 mm, the particle size of the gangue in the present invention can reach up to 20 mm at most. The present invention is conducive to reducing the crushing cost of gangue and improving the overall efficiency of the mine;
[0033] (4) The carbon sequestration rate of the negative carbon filling material of the present invention is high, which can reach up to 42.56%. This is because the high porosity of the CGIF negative carbon filling material of the present invention better ensures the high adsorption of CO2; at the same time, the Ca contained in the CGIF negative carbon filling material of the present invention 2+ Mg 2+ , K + 、Al 3+Alkali metal elements such as carbon dioxide will react with CO2, thereby chemically fixing CO2 and further improving the carbon storage rate.
[0034] (5) According to calculations, mining one ton of raw coal produces 0.74 m 3 The goaf, based on the negative carbon filling material of the present invention, can produce 945 to 1.845 billion tons of negative carbon, based on the annual mining of 4.5 billion tons of raw coal. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A structural model diagram of a CGIF negative carbon filling material according to some embodiments;
[0036] Figure 2 is a three-dimensional diagram of a negative carbon filling material mold according to some embodiments;
[0037] Figure 3 for Figure 2 A top view or bottom view of a negative carbon filling material mold. DETAILED DESCRIPTION
[0038] In some embodiments, a negative carbon filling material is provided, such as Figure 1 As shown, it includes loose coal gangue 1 and cementitious material 2, the particle size of the loose coal gangue 1 is 0-20mm, the cementitious material 2 is attached to the surface of the loose coal gangue 1 in the form of flocs, and the key contact points between the particles of the loose coal gangue 1 are bonded by the cementitious material 2, and the loose coal gangue 1 and the cementitious material 2 are connected layer by layer to form a coal gangue-colloid composite porous material with a porosity of not less than 30% and a uniaxial compressive strength of not less than 0.46MPa, that is, a negative carbon filling material; the porous structure in the negative carbon filling material can be used to store CO2 3, and the CO2 storage rate is not less than 25%; wherein: the slump of the cementitious material is between 170 and 200mm, the initial setting time is less than 15min, the final setting time is less than 3h, and it has fast and efficient bonding and is not easy to flow.
[0039] In the above embodiment, the cementitious material 2 with a slump between 170 and 200 mm, an initial setting time of less than 15 minutes, and a final setting time of less than 3 hours has the characteristics of high viscosity and poor fluidity. The loose coal gangue 1 interacts with the cementitious material 2 to form a strong cementation effect between the key contact points between the particles of the loose coal gangue 1, and finally forms a coal gangue-colloid composite porous material filling body with more pores and a stable overall structure. The porous space of the negative carbon filling material is used to achieve the structural storage effect of CO2 3, and the structural strength of the 0-20 mm coarse-grained coal gangue and the bonding effect of the cementitious material are used to achieve the high porosity, low density and high strength bearing of the negative carbon filling material.
[0040] Different from the existing cementing filling materials in which the particle size of the gangue does not exceed 10 mm, the particle size of the gangue in the above embodiment can reach up to 20 mm at most. The present invention is beneficial to reducing the crushing cost of the gangue and improving the overall efficiency of the mine.
[0041] The carbon sequestration rate of the negative carbon filling material in the above embodiment is high, up to 42.56%. This is because the high porosity of the CGIF negative carbon filling material of the present invention better ensures the high adsorption of CO2; at the same time, the Ca contained in the CGIF negative carbon filling material of the present invention 2+ Mg 2+ , K + 、Al 3+ Alkali metal elements such as carbon dioxide will react with CO2, thereby chemically fixing CO2 and further improving the carbon storage rate.
[0042] In some embodiments, the cementitious material includes the following components, by mass: 100-140 parts of fly ash, 10-15 parts of cement, 70-90 parts of quicklime, 1.5-2.5 parts of cement early strength activator, 3-5 parts of accelerator and 50-60 parts of water.
[0043] In some embodiments, the cementitious material includes the following components, measured in parts by mass: 120 parts of fly ash, 10 parts of cement, 80 parts of quicklime, 2 parts of cement early strength activator, 4 parts of accelerating agent and 54 parts of water.
[0044] In some embodiments, the bulk coal gangue is obtained by sorting coal gangue with a particle size of ≤200 mm in a mining area or crushing coal gangue accumulated on the surface.
[0045] In some embodiments, a method for preparing the aforementioned negative carbon filling material is provided, comprising the following steps:
[0046] (1) According to the target porosity of the negative carbon filling material, in the negative carbon filling material mold 7 (such as Figure 2 and Figure 3 The coal gangue of a certain particle size is filled in the water (as shown);
[0047] (2) closing the slurry discharge hole 9 at the bottom 8 of the negative carbon filling material mold 7, and injecting liquid / supercritical CO2 from the slurry injection hole 5 at the top 4 of the negative carbon filling material mold 7; recording the CO2 injection volume V1, and calculating the carbon sequestration rate Ф of the negative carbon filling material;
[0048] (3) injecting cementitious material from the grouting hole 5 at the top 4 of the negative carbon filling material mold 7 until the cementitious material fills the negative carbon filling material mold 7;
[0049] (4) opening the slurry discharge hole 9 at the bottom 8 of the negative carbon filling material mold 7 to discharge excess gelling material to obtain a negative carbon filling material sample;
[0050] (5) After the negative carbon filling material sample is placed in a curing box and cured for 1 hour, the uniaxial compressive strength σ and porosity θ of the negative carbon filling material are tested;
[0051] (6) By changing the particle size distribution of the loose coal gangue in step (1) to change the target porosity of the negative carbon filling material, repeating steps (2) to (5), a prediction model between the porosity θ, CO2 storage rate Φ and uniaxial compressive strength σ of the negative carbon filling material is established, as shown in the following formula:
[0052] σ=F(θ,Φ);
[0053] (7) According to step (6), the particle size distribution of loose coal gangue corresponding to the method of negative carbon filling material with a porosity θ not less than 30%, a uniaxial compressive strength not less than 0.46 MPa and a CO2 storage rate not less than 25% is screened out.
[0054] In some embodiments, the negative carbon filling material mold 7 is transparent, which facilitates observation of the state of the loose coal gangue and cementitious material inside.
[0055] In some embodiments, the negative carbon filling material mold 7 is a standard cube with a side length of 70.7 mm.
[0056] In some embodiments, the top 4 grouting holes 5 and the bottom 8 grouting holes 9 of the negative carbon filling material mold 7 are round holes, the number of the top 4 grouting holes 5 and the bottom 8 grouting holes 9 are 5 respectively, and the top 4 grouting holes 5 and the bottom 8 grouting holes 9 can be opened and closed.
[0057] In some embodiments, the diameter of the top 4 grouting holes 5 and the bottom 8 grouting holes 9 is 6 mm.
[0058] In some embodiments, in step (2), when injecting liquid / supercritical CO2, if the local pressure is too high and the liquid / supercritical CO2 is difficult to inject, then other top 4 grouting holes 5 are replaced to continue injecting liquid / supercritical CO2;
[0059] In some embodiments, in step (3), when injecting the cementitious material, the cementitious material is injected sequentially from the grouting holes 5 at different positions of the top 4 to improve the distribution uniformity of the cementitious material in the negative carbon filling material mold 7.
[0060] Example 1
[0061] A method for preparing a CGIF negative carbon filling material comprises the following steps:
[0062] Step 1: Fill the negative carbon filling material mold 7 with loose coal gangue 1 with particle sizes of 0-10 mm, 0-15 mm, and 0-20 mm respectively;
[0063] Step 2: Prepare cementitious materials according to the following mass ratio: 120 parts of fly ash, 10 parts of cement, 80 parts of quicklime, 2 parts of cement early strength activator, 4 parts of accelerating agent and 54 parts of water;
[0064] Step 3: Close the slurry discharge hole 9 at the bottom 8 of the negative carbon filling material mold 7, and inject liquid / supercritical CO2 from the grouting hole 5 at the top 4 of the negative carbon filling material mold 7; record the CO2 injection volume V1, and calculate the carbon sequestration rate Ф of the negative carbon filling material according to the following formula, where the internal volume V2 of the mold is 70.7×70.7×70.7mm 3 =3.53×10 -4 m 3 :
[0065]
[0066] Step 4: injecting the cementitious material from the grouting hole 5 at the top 4 of the negative carbon filling material mold 7 until the cementitious material fills the negative carbon filling material mold 7;
[0067] Step 5: Open the slurry discharge hole 9 at the bottom 8 of the negative carbon filling material mold 7 to discharge excess gelling material to obtain a negative carbon filling material sample;
[0068] Step 6: After the negative carbon filling material sample is placed in a curing box for curing for 1 hour, the uniaxial compressive strength σ and porosity θ of the negative carbon filling material are tested;
[0069] Step 7: Change the particle size distribution of the loose coal gangue to change the target porosity of the negative carbon filling material, repeat the above steps, and establish a prediction model between the porosity θ, CO2 storage rate Ф and uniaxial compressive strength σ of the negative carbon filling material.
[0070] In this embodiment, the uniaxial compressive strength σ of the negative carbon filling material is tested in accordance with the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016), and the porosity θ of the negative carbon filling material is tested by mercury injection. The performance parameters of the negative carbon filling material prepared under different porosity conditions are shown in Table 1.
[0071] Table 1 Performance parameters of CGIF negative carbon filling materials under different porosity conditions
[0072]
[0073] It can be seen from Table 1 that based on the preparation method of the present invention, as the particle size range of coal gangue increases, the porosity of the obtained CGIF negative carbon filling material gradually increases, while the uniaxial compressive strength decreases accordingly, and the CO2 storage rate gradually increases.
[0074] By gradually enriching the porosity, uniaxial compressive strength and CO2 storage rate of coal gangue with different particle sizes through the above steps, a prediction model between the porosity θ, CO2 storage rate Ф and uniaxial compressive strength σ of negative carbon filling materials can be gradually constructed.
[0075] According to calculations, mining one ton of raw coal produces 0.74m 3 In the goaf, when the porosity θ of the negative carbon filling material is 30%, 0.21 tons of supercritical CO2 can be sealed; when the porosity is 50%, 0.34 tons of supercritical CO2 can be sealed; when the porosity is 60%, 0.41 tons of supercritical CO2 can be sealed. Based on the annual mining of 4.5 billion tons of raw coal, 945 to 1.845 billion tons of negative carbon can be stored.
Claims
1. A method for preparing a negative carbon filling material, characterized in that: The negative carbon filling material comprises loose coal gangue and a cementitious material, wherein the particle size of the loose coal gangue is 0 to 20 mm, the cementitious material is attached to the surface of the loose coal gangue in a flocculent state, and the key contact points between the particles of the loose coal gangue are bonded by the cementitious material, and the loose coal gangue and the cementitious material are connected layer by layer to form a coal gangue-colloid composite porous material with a porosity of not less than 30% and a uniaxial compressive strength of not less than 0.46 MPa, i.e., a negative carbon filling material; the porous structure in the negative carbon filling material can be used to store CO2, and the CO2 storage rate is not less than 25%, wherein the slump of the cementitious material is between 170 and 200 mm, the initial setting time is less than 15 min, and the final setting time is less than 3 h, and the preparation method of the negative carbon filling material comprises the following steps: (1) according to the target porosity of the negative carbon filling material, filling the negative carbon filling material mold with the loose coal gangue of a certain particle size distribution; (2) closing the bottom grouting hole of the negative carbon filling material mold, and injecting liquid / supercritical CO2 from the top grouting hole of the negative carbon filling material mold; recording the CO2 injection volume V1, and calculating the carbon sequestration rate Φ of the negative carbon filling material; (3) injecting the cementitious material from the top grouting hole of the negative carbon filling material mold until the cementitious material fills the negative carbon filling material mold; (4) opening the bottom slurry discharge hole of the negative carbon filling material mold to discharge excess cementitious material to obtain the negative carbon filling material sample; (5) After the negative carbon filling material sample is placed in a curing box and cured for 1 hour, the uniaxial compressive strength σ and porosity θ of the negative carbon filling material are tested; (6) By changing the particle size distribution of the loose coal gangue in step (1) to change the target porosity of the negative carbon filling material, repeating steps (2) to (5), a prediction model between the porosity θ, CO2 storage rate Φ and uniaxial compressive strength σ of the negative carbon filling material is established, as shown in the following formula: σ=F(θ,Φ); (7) According to step (6), the particle size distribution of the loose coal gangue corresponding to the method of selecting the negative carbon filling material having a porosity θ not less than 30%, a uniaxial compressive strength σ not less than 0.46 MPa and a CO2 storage rate Φ not less than 25% is selected.
2. The method for preparing a negative carbon filling material according to claim 1, characterized in that: The cementitious material comprises the following components, by weight: 100-140 parts of fly ash, 10-15 parts of cement, 70-90 parts of quicklime, 1.5-2.5 parts of cement early strength activator, 3-5 parts of accelerating agent and 50-60 parts of water.
3. The method for preparing a negative carbon filling material according to claim 2, characterized in that: The cementitious material comprises the following components, by mass: 120 parts of fly ash, 10 parts of cement, 80 parts of quicklime, 2 parts of cement early strength activator, 4 parts of accelerating agent and 54 parts of water.
4. The method for preparing a negative carbon filling material according to claim 3, characterized in that: The particle size gradation of the loose coal gangue is 0 to 20 mm.
5. The method for preparing a negative carbon filling material according to claim 3, characterized in that: The particle size gradation of the loose coal gangue is 0-10 mm; the obtained negative carbon filling material has a porosity θ of not less than 30%, a uniaxial compressive strength σ of not less than 0.6 MPa, and a CO2 storage rate Φ of not less than 25%.
6. The method for preparing a negative carbon filling material according to claim 3, characterized in that: The particle size gradation of the loose coal gangue is 0-15 mm; the obtained negative carbon filling material has a porosity θ of not less than 49%, a uniaxial compressive strength σ of not less than 0.5 MPa, and a CO2 storage rate Φ of not less than 36%.
7. The method for preparing a negative carbon filling material according to claim 3, characterized in that: The color of the negative carbon filling material mold is transparent.
8. The method for preparing a negative carbon filling material according to claim 3, characterized in that: The top grouting holes and the bottom grouting holes of the negative carbon filling material mold are circular holes, the number of the top grouting holes and the number of the bottom grouting holes are 5 respectively, and the top grouting holes and the bottom grouting holes can be opened and closed.
9. The method for preparing a negative carbon filling material according to claim 8, characterized in that: In step (2), when injecting liquid / supercritical CO2, if the local pressure is too high and the liquid / supercritical CO2 is difficult to inject, then other top grouting holes are replaced to continue injecting liquid / supercritical CO2; In step (3), when injecting the cementitious material, the cementitious material is injected sequentially from top grouting holes at different positions to improve the distribution uniformity of the cementitious material in the negative carbon filling material mold.
Citation Information
Patent Citations
Mine solid waste fluidization filling treatment and carbon dioxide sealing method
CN115628106A